The urban wooden house and its fate - Nashchokina, Maria (project baikal, 2021)
Wooden architecture is regarded as a basis for Russian cultural identity. A short journey into the history of its preservation is made. The design and practical experiences of Irkutsk, Tomsk, Nyandoma and Tallinn are viewed as contemporary examples of preservation of wooden urban houses. The author considers starting demolition of the unique workers’ settlement Chagoda built from wood in the constructivist style to be one of the recent losses. The article points out the necessity of cardinal public reevaluation of national values and a traditional Russian wooden house.
Keywords: urban wooden house; museefication of wooden structures in the USSR; 130 Quarter in Irkutsk; projects of preservation and reconstruction of wooden houses in Tomsk and Nyandoma; reconstruction of Kalamaja neighborhood in Tallinn; Chagoda settlement